2007
DOI: 10.1167/iovs.06-1282
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes in Optic Nerve Head Gene Expression after Exposure to Elevated Intraocular Pressure in a Rat Glaucoma Model

Abstract: In the ONH, pressure-induced injury results in cell proliferation and dramatically altered gene expression. For specific genes, expression levels were most altered by focal injury, suggesting that further array studies may identify initial, and potentially injurious, altered processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
228
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(251 citation statements)
references
References 103 publications
21
228
1
1
Order By: Relevance
“…[39][40][41] Advances in biochemistry, chemistry, and engineering have enabled the development of new gene expression assays. 42 44 used microarray analysis to identify gene expression changes in the pressure-injured optic nerve head (ONH) in a rat glaucoma model. They found that the most significantly affected gene classes were cell proliferation, immune response, lysosome, cytoskeleton, extracellular matrix, and ribosomal.…”
Section: Genetic Terms and Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] Advances in biochemistry, chemistry, and engineering have enabled the development of new gene expression assays. 42 44 used microarray analysis to identify gene expression changes in the pressure-injured optic nerve head (ONH) in a rat glaucoma model. They found that the most significantly affected gene classes were cell proliferation, immune response, lysosome, cytoskeleton, extracellular matrix, and ribosomal.…”
Section: Genetic Terms and Approachesmentioning
confidence: 99%
“…The putative mechanisms of how this occurs are legion. They include pressureinduced injury of the ONH, leading to retinal gene expression alterations, 44,141 astrocyte response to changes in IOP, 142 oxidative stress, mitochondrial dysfunction, neurotrophic factors, 143,144 and autoimmunity. 145 Identifying validated genetic mutations that are replicated in multiple populations perhaps offers the best hope of correct identification of the most important pathways, which result in RGC death.…”
Section: Therapeutic Implications Of Genetics For Poagmentioning
confidence: 99%
“…2, 15, 23). These studies identified changes in multiple genes/pathways related to immune responses, as well as structural and inflammatory changes in the ONH (8,24,25). The cause and impact of most of these changes in glaucoma remain to be determined, however.…”
mentioning
confidence: 99%
“…Increase in collagen VI has also been proposed to increase the rate of collagen type I fibril formation (Harumiya et al, 2002;Minamitani et al, 2004;), result in loss of elastic properties (Hatamochi et al, 1996) and contribute to migration of glioblastoma cells . Elevated IOP models of glaucoma have demonstrated, the deposition of collagen I and VI at the optic nerve head to be an early event and are correlated linearly to degree of IOP-induced injury (Johnson et al, 2000;Guo et al, 2005;Morrison et al, 2005;Johnson et al, 2007). The ability of LC cells to respond to profibrotic triggers such as mechanical stress and transforming growth factor-β (TGF-β) resulting in enhanced ECM synthesis, implicates LC as an important pro-fibrotic tissue that could lead to loss of structural integrity resulting in collapse of LC and associated neuronal loss in gluacoma (Hernandez 2000 and.…”
Section: Discussionmentioning
confidence: 99%